The Impact of the Concept of Continental (Romano-Germanic) Criminal Procedure on the Phenomenon of “Epistemic Injustice” - Maria Rogacka-Rzewnicka (Revista Brasileira de Direito Processual Penal)
The present article concentrates on the systemic and institutional environment characteristic of the sphere of criminal trial as being a source of reality called “epistemic injustice”. The subject of this analysis is criminal procedure applicable in continental Europe. In this attempt to transpose the concept of “epistemic injustice” coined by Miranda Ficker to criminal procedure, certain specific systemic and institutional solutions were accentuated, which may contribute to injustice in relation to different aspects of the procedure. Three important institutions regulating criminal procedure were taken into account: the concept of prosecuting crimes, procedural consensualism, and the crime victim. The conclusions are not based on hard arguments that would directly prove the phenomena described by M. Fricker. It was concluded that “epistemic injustice” is more a matter of the facts than the law, although – as it was attempted to show – particular legal solutions may in a specific manner contribute to the state designated by that term. The presented threats are comprised mainly in the reality termed in literature as “epistemic agential injustice”.